Mesoporous Fe2O3-TiO2 integrated with plasmonic Ag nanoparticles for enhanced solar H2 production - Mani, Sunesh S.; Rajendran, Sivaraj; Saju, Simi; Babu, Bindhya M.; Mathew, Thomas; Gopinath, Chinnakonda S. (Chemistry-An Asian Journal, 2025)
Present work describes a sol-gel assisted one-pot synthesis of mesoporous Fe2O3-TiO2 nanocomposites (TiFe) with different Ti : Fe ratios, and fabrication of Ag-integrated with TiFe nanocomposites (TiFeAg) by a chemical reduction method and demonstrated for high solar H2 generation activity in direct sunlight. Enhanced solar H2 production is attributed to the light absorption from entire UV+Visible region of solar spectrum combined with Schottky (Ag-semiconductor) and heterojunctions (TiO2-Fe2O3), as evidenced from HRTEM and various characterization studies. TiFeAg-2 thin film (1 wt % Ag-loaded TiFe-4) displayed the highest activity with a solar H2 yield of 7.64 mmol h-1g-1, which is 48 times higher than that of bare TiO2 and 5 times higher in thin film form compared to its powder counterpart. Schottky and heterojunctions formed at the interface efficiently separate the charge carriers and increase the hydrogen production activity. The highest H2 production activity of TiFeAg-2 is partly attributed to the heterogeneous distribution of Fe3+ and metallic Ag-species with relatively high Ag/Ti surface atomic ratio. A plausible photocatalytic reaction mechanism on TiFeAg nanocomposite may involve the direct electron transfer from both Fe2O3 and TiO2 to Ag nanoparticles which are subsequently utilized for the reduction of H+ to H2.
Keywords: energy conversion; green hydrogen; Photocatalysis; Solar harvesting; water splitting

Multifunctional NiO/Ti3+-TiO2 for concurrent water reduction and glycerol oxidation to value added products by sunlight driven photocatalysis - Rajendran, Sivaraj; Saju, Simi; Mani, Sunesh S.; Asoka, Anantha Krishnan; Saha, Arindam; Arun, Pushkaran S.; Ghosh, Biplab; Mathew, Thomas; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2025)
The present work describes the synthesis of bifunctional-mesoporous-self-doped Ti3+ containing NiO/TiO2 photocatalysts for concurrent utilization of e- and h+ to produce H2 and value-added products (VAPs), respectively, from aqueous glycerol. UV-vis diffuse reflectance results and band gap analysis revealed an improved light absorption due to integration of Ni2+ with Ti3+/TiO2. Various electrochemical, PL and TRPL spectral analyses demonstrate p-n heterojunction formation between NiO and Ti3+-TiO2, which enhances charge separation and helps in achieving improved activity. HRTEM analysis of NiO/Ti3+-TiO2 nanocomposites revealed that NiO is highly dispersed on TiO2 with interfacial heterojunctions between them. XPS results demonstrate the partial reduction of Ti4+ to Ti3+ and Ni-Ti synergetic interaction in NiO/TiO2 to form NiO/Ti3+-TiO2 nanocomposites. EXAFS studies show that the Ni-O bond distance is similar to that of NiTiO3 suggesting electronic integration of components of the photocatalyst by forming a Ni2+-O-Ti3+/Ti4+ lattice network. Ni2+/Ti3+-TiO2 nanocomposites as a bifunctional photocatalyst exhibited significantly enhanced activity in H2 production and conversion of glycerol to VAPs, namely, glycolaldehyde, 1,3-dihydroxyacetone, and formic acid; formation of these products highlights not only oxidation, but also C-C cleavage of glycerol. The NiO/Ti3+-TiO2 photocatalysts fabricated in thin film form displayed higher photocatalytic efficiency than their powder counterpart. Among NiO/Ti3+-TiO2 nanocomposites NiT-3 exhibits the highest H2 yield at 15.62 mmol h-1 g-1, which is 38 times higher than that of bare TiO2. The enhanced photocatalytic activity is ascribed to the high charge carrier density, the synergistic interaction between Ni2+ and Ti3+-TiO2, formation of a p-n heterojunction at the interface between NiO and Ti3+-TiO2 and effective utilization of charge carriers for redox reactions.

Multifunctional NiO/Ti3+–TiO2 for concurrent water reduction and glycerol oxidation to value added products by sunlight driven photocatalysis - Rajendran, Sivaraj; Saju, Simi; Mani, Sunesh S.; Asoka, Anantha Krishnan; Saha, Arindam; Arun, Pushkaran S.; Ghosh, Biplab; Mathew, Thomas; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2025)
The present work describes the synthesis of bifunctional-mesoporous-self-doped Ti3+ containing NiO/TiO2 photocatalysts for concurrent utilization of e− and h+ to produce H2 and value-added products (VAPs), respectively, from aqueous glycerol. UV-vis diffuse reflectance results and band gap analysis revealed an improved light absorption due to integration of Ni2+ with Ti3+/TiO2. Various electrochemical, PL and TRPL spectral analyses demonstrate p–n heterojunction formation between NiO and Ti3+–TiO2, which enhances charge separation and helps in achieving improved activity. HRTEM analysis of NiO/Ti3+–TiO2 nanocomposites revealed that NiO is highly dispersed on TiO2 with interfacial heterojunctions between them. XPS results demonstrate the partial reduction of Ti4+ to Ti3+ and Ni–Ti synergetic interaction in NiO/TiO2 to form NiO/Ti3+–TiO2 nanocomposites. EXAFS studies show that the Ni–O bond distance is similar to that of NiTiO3 suggesting electronic integration of components of the photocatalyst by forming a Ni2+–O–Ti3+/Ti4+ lattice network. Ni2+/Ti3+–TiO2 nanocomposites as a bifunctional photocatalyst exhibited significantly enhanced activity in H2 production and conversion of glycerol to VAPs, namely, glycolaldehyde, 1,3-dihydroxyacetone, and formic acid; formation of these products highlights not only oxidation, but also C–C cleavage of glycerol. The NiO/Ti3+–TiO2 photocatalysts fabricated in thin film form displayed higher photocatalytic efficiency than their powder counterpart. Among NiO/Ti3+–TiO2 nanocomposites NiT-3 exhibits the highest H2 yield at 15.62 mmol h−1 g−1, which is 38 times higher than that of bare TiO2. The enhanced photocatalytic activity is ascribed to the high charge carrier density, the synergistic interaction between Ni2+ and Ti3+–TiO2, formation of a p–n heterojunction at the interface between NiO and Ti3+–TiO2 and effective utilization of charge carriers for redox reactions.